Spatial epidemiology of chronic wasting disease in Colorado mule deer (Odocoileus hemionus) - Farnsworth, Matthew Lee, author (Colorado State University. Libraries, 2004)
I conduct three separate studies using the spatial distribution of chronic wasting disease (CWD) in Colorado mule deer (Odocoileus hemionous) to examine the relationship between individual level infection probability and several biotic and abiotic components of the system. The models I develop are focused on: (1) examining the role of human induced land use change in exacerbating the disease; (2) the scales of mule deer seasonal movement patterns that correspond best to the observed distribution of CWD infection; and (3) the relationship between deer density and infection risk. These analyses address the known effects of age and sex, and in one study, I consider the effects of land ownership and habitat. All studies use contemporary information theoretic approaches; either Akaike's Information Criteria (AIC) or its Hierarchical Bayesian analogue, the Deviance Information Criteria (DIC), to determine the strength of support for candidate models representing various hypotheses about the proposed relationships. The results suggest a positive relationship between human land use and land ownership patterns and infection risk. My analyses also suggest that the spatial distribution of CWD corresponds best to a highly localized infection process, however I am unable to detect a relationship between deer density and infection risk. I conclude by addressing several issues associated with using the data as I have for retrospective analysis and provide management recommendations based on my findings. Finally, I extend the discussion to address future avenues of research that might benefit from the work presented in this dissertation.
Keywords: ecology; forestry